Potential Impact of Aedes Albopictus (Skuse,1894), an Arbovirus and Nematode Vector, on Human Public Health - J. dos Santos Grácio, António; Amélia Grácio, Maria (Journal of Public Health International, 2019)
A review outlines the ecology and public health implications of Aedes albopictus as a vector of arboviruses and nematodes. Surveillance and control strategies are discussed.
Keywords: Aedes Albopictus; Arbovirus Vector; Nematode Vector; Vector-Borne Diseases; Public Health